The Philosophical Dimension of Anthropology - Cabada Castro, Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The article purports to elucidate the meaning of philosophical anthropology as a reflection that should not evade the tension and inevitable ambiguity that the treatment of a theme about the human being, essentially indefinable and non-objectifiable, entails. From this viewpoint, the article analyzes, on one hand, the relation of philosophical anthropology with other anthropologies that, in principle, are non-philosophical; and alludes, on the other, to the actual and future tasks that philosophical anthropology should face.